Damage detection of PVC (Poly Vinyl Chloride) and ABS (Acrylonitrilebutadiene-Strryrene) pipe using non destructive vibration testing - Mohd Haris Md Mahiyuddin
This paper will review a technique use to detect cracks in long pipes. Experimental setup are performed by using two different materials; PVC (Poly Vinyl Chloride) and ABS (Acrylonitrilebutadiene-Strryrene) pipe with the crack to thickness ratio in the range 0.20 m and 0.4 m are investigated.